Internalized and Externalized Problematics in Pre-schoolers and their Association to the Emotional State of their Caregivers, before and During COVID-19 Quarantine - Herazo-Chamorro, Mónica; Pérez-Vásquez, Diego; Bolaños-Torres, Bertha; Fonseca-Beltrán, Leodanis; Romero-Acosta, Kelly; Restrepo-Ruiz, Marisela (Journal of Ecohumanism, 2024)
This research aims at determining the internal and external problematics from two to five years old kids face and its association to their caregivers’ emotional state, before and during COVID-19 quarantine. Regarding the methodology of the study, this is a correlational study with a quantitative scope. Ninety six (96) caregivers participated on it; and the instruments applied were a sociodemographic data questionnaire, a screening questionnaire for depressive and anxious symptoms for adults, and a screening questionnaire for one and a half to five years old kids. With respect to results, the preschoolers presented more internalizing and externalizing symptoms during quarantine than before confinement. About caregivers’ emotional state before and during the quarantine, this was related to the kids’ symptoms in both phases. Concerning conclusions, two to five years old children presented more symptoms during confinement due to COVID-19. It is necessary to conduct studies that observe the existence of emotional and behavioral problems in preschoolers after quarantine because of COVID-19.